Audioleyendas guaneñas, en el desarrollo del lenguaje oral de los niños de inicial 2, de la Unidad Educativa La Maná, cantón La Maná, provincia de Cotopaxi. Período 2022 - Guevara Guevara, Nancy Patricia (2023)
ABSTRACT: Culture and Language share a strong link, and both of them evolve according to human kind evolution. Man is a social entity, and throughout the years has used language to exchange knowledge. The acquisition of a set of language skills becomes a necessity, for a preschool child, the appropriate development of language is essential because this is the bridge to access and build knowledge in the future. A countless number of tools can be used to promote language skills progress, however, in this research, we prioritized the use of legends, as a part of verbal traditional Literature that preserve a culture of a population alive; additionally, they serve as a teaching instrument to stimulate verbal language. This research has the main objective to analyze the contribution of the teaching guide with audio-legends from Guano, to enhance verbal language in Preschool children in La Maná Public School. To achieve this objective, a first diagnose on the initial verbal language level of children performed, this process evidenced a delay in three dimensions: form, content and use. Therefore, the design a teaching guide with audio-legends from Guano to motivate verbal language development in 29 children from Preschool second level “A” took place. The application of the guide took place during nine weeks, and a second evaluation taken. This time, most of the children scored in the normal standard in the three language dimensions. This research counts with a quantitative approach, a non-experimental design, and it achieved a propositional level. Chi square method proved the hypothesis, accepting that Guano audio-legends instrument potentiates verbal language development in children from Preschool education level. The use of this teaching guide accomplished its purpose, consequently, it recommended to implement it for children’s verbal language development in other children from similar age.